Incidencia del pensamiento marxista en la pedagogía liberadora de Paulo Freire. - Ordóñez Abad, Luis Enrique (2016)
Incidence of Marxist thought in the liberating pedagogy of Paulo Freire helped to lay the foundations for the development of philosophical and pedagogical movements in Latin America. It is intended by the following academic article; identify the links between the main concepts of Marxism with its applicability in the South American social and educational context. From this perspective it is valid to analyze the approaches that allowed to legitimate pedagogical proposal of Paulo Freire. In the first section the great contributions of the main Marxist authors (Mariátegui, Mella, etc.) try to understand the historical and cultural premises that allowed the consolidation of critical thinking in Latin America, whose authors adapted Marxist analysis to the interpretation of our reality. In the second section, we seek to rethink the fundamentals of South American education and create a new praxis which challenges the social and cultural reproduction that consolidated the hegemonic domination of social injustice. In the third section, it focuses to look at the contributions of Marxism to the pedagogy of Paulo’s Freire liberation, and the remaining challenges for our context in the XXI century.